Short‐term postoperative non‐supine positioning versus strict face‐down positioning in macular hole surgery. (25th July 2012) - Forsaa, Vegard Asgeir; Raeder, Sten; Hashemi, Laila Tjelta; Krohn, Jørgen
Abstract. Purpose: The purpose of this study was to compare the efficacy of short‐term non‐supine positioning (NSP) and strict face‐down positioning (FDP) in the repair of macular hole (MH). Methods: We retrospectively reviewed all MH repairs over a 27‐month period (2008–2010). Inclusion criteria were idiopathic full thickness stage 2–4 MH treated by a single surgeon with 23‐gauge pars plana vitrectomy, internal limiting membrane peeling and gas tamponade, followed by postoperative short‐term NSP (for 5 days) or strict FDP (for 3–4 days). NSP was achieved by fastening a tennis ball to the back of the nightshirt. Outcome measures were anatomical MH closure verified by optical coherence tomography and postoperative visual acuity. Results: A total of 67 eyes (64 patients) met the inclusion criteria. The median follow‐up period was 6.6 months (range, 4.7–19.8 months). The closure rates following a single operation were 30/33 (90.9%) in the FDP group, and 31/34 (91.2%) in the NSP group, respectively (p = 0.97). The FDP group improved 2.9 ETDRS lines, and 23 eyes (69.7%) gained two or more ETDRS lines. The NSP group improved 2.7 ETDRS lines (p = 1.00), and 25 eyes (73.5%) gained two or more ETDRS lines. The closure rates in the MH subgroup with diameters larger than 400 μm were 20/23 (87.0%) and 15/17 (88.2%) in the FDP group and the NSP group, respectively (p = 0.96). Conclusion: The study indicates that short‐term NSP is equally effective as strict FDP in the repair of MH. Contrary to previous reports, even large MH did not seem to benefit from FDP.